Community Empowerment Through the Kampung Pangan Madani Social Innovation Program - Riyadiyanto; Istiqomah (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
The research method in this article uses a qualitative descriptive approach with data collection techniques using interviews, observation and documentation studies. data validity using source triangulation. This article concludes at least the first few points, in practice the Kampung Pangan Madani Program is managed by two groups, namely the Processed Group and the Catfish Cultivation Group. The Processed Group has activities for planting and managing hydroponic plants while the Catfish Cultivation Group has activities for caring for and harvesting catfish. Apart from that, the existence of the Kampung Pangan Madani Program also produces a value chain where there is a link between one activity and another as explained above. In fact, this program can be categorized as a social innovation which has produced added value for society and the environment so as to realize energy efficiency. Lastly, to ensure the results of this program, there is a compass for the sustainability of the Kampung Pangan Madani Program, in which the program results are grouped based on four elements, namely nature, wellbeing, economy, and social.